Fabrication of disposable gold macrodisc and platinum microband electrodes for use in room-temperature ionic liquids. - Xiong, L; Lowinsohn, D; Ward, K; Compton, R (2013)
We report a simple and facile methodology for constructing gold macrodisc and platinum microband electrodes for use in room temperature ionic liquids (RTILs). To validate the use of gold macrodisc electrodes, the voltammetry of Ru(NH3)6(3+) was studied in 0.1 M aqueous KCl. The Randles-Ševčík equation was used to calculate the diffusion coefficient, giving excellent agreement with literature values, suggesting that the gold macrodisc electrode is capable of performing quantitative electroanalysis in aqueous media. Gold macrodisc electrodes were used to study oxidation of ferrocene in N-butyl-N-methylpyrrolidinium bis(fluoromethylsulfonyl)imide ([C4mpyrr][NTf2]) using cyclic voltammetry. The diffusion coefficient of ferrocene, (2.43 ± 0.07) × 10(-11) m(2) s(-1), was obtained. This value is very close to the literature value, indicating good performance of gold electrodes in RTILs. Platinum microband electrodes were tested in 1-propyl-3-methylimidazolium bis-trifluoromethylsulfonylimide ([Pmim][NTf2]) containing decamethylferrocene. Diffusion coefficients and electron transfer rates were obtained by fitting relevant simulations to the experimental data. For comparison, analogous experiments and analyses were performed on a commercial platinum microdisc, where the results obtained from both microdisc and microband agree well, further suggesting that the platinum microband electrode is suitable to be used in RTILs. Finally, gold macrodisc and platinum microband electrodes were used for oxygen detection. Gold macrodisc electrodes were used to find the peak currents of oxygen at each volume percentage analysed. Platinum microband electrodes showed steady-state currents of different volumes of oxygen. These two results are compared which resulted in excellent agreement. This is further confirmed by studying Henry's law constants obtained from both electrodes. The excellent behaviour of these two fabricated electrodes suggests that they are suitable for quantitative measurements and practicable for real world applications.